Factorial Validity of Maslach Burnout Inventory Human Services (Mbi-Hss) in Chilean Professionals [Validez Factorial del Maslach Burnout Inventory Human Services (Mbi-Hss) en Profesionales Chilenos] - Mena-Miranda, L; Olivares-Faundez, V (Pontificia Universidad Javeriana, 2014)
The present study tested the factorial validity of an adjustment to the Spanish language of the Maslach Burnout Inventory in a sample of 957 professionals of Chilean services of different labour units. The reliability and factor structure of the MBI were investigated. Exploratory and confirmatory factors analysis indicated that the original three-factor model of the MBI fit well with both the data and the Root Mean Standar Error of Aproximation (RMSEA) value, although the items 12, 13, 14, 20 and 21 presented an inadequate behavior in the original factorial resultant, so they were eliminated. The internal consistency of the dimensions of the inventory was acceptable, although the Depersonalization subscale was relatively low. So far, the resultsobtained show that the questionnaire appears to be valid and reliable in the version adapted to the Spanish language.